Sufficiency Economy and Circular Agriculture: A Model for Sustainable and Carbon-Neutral Agriculture in Thailand - Lounkaew, Kiatanantha (Journal of Dhamma for Life, 2024)
This article presents the integration of the Sufficiency Economy Philosophy, circular agriculture, and the pursuit of carbon neutrality in Thailand’s agricultural sector. The objective is to explore sustainable and environmentally friendly agricultural system development approaches. This research employs literature review and case study analysis methods. The findings reveal that the principles of the Sufficiency Economy Philosophy, comprising moderation, reasonableness, and self-immunity, can serve as a crucial foundation for developing agricultural systems that reduce greenhouse gas emissions and increase carbon sequestration. When combined with circular agriculture concepts, which emphasize efficient resource use and waste reduction, these principles offer a promising pathway. Case studies from Thailand, such as the New Theory Agriculture, integrated farming systems, and organic farming, demonstrate the feasibility of applying these concepts. However, the transition to a carbon-neutral agricultural system still faces economic, technical, and social challenges. This article proposes policy and practical recommendations to promote sustainable and environmentally friendly agricultural development in Thailand.